The Phoenician-Punic Necropolises Djebila and Aïn Dalia Kebira (Tangier Region, Morocco) - Blaschta, Dirk; Mederos Martín, Alfredo; Yahia , Saousanne; El Mhassani , Mohamed; Odriozola Lloret , Carlos P.; Garrido Cordero , José Ángel; Martínez-Blanes , José María (Madrider Mitteilungen, 2024)
The cemeteries of Djebila (DJ) and Aïn Dalia Kebira (AD) are the largest Phoenician-Punic necropolises in Morocco. Although they are very similar in appearance, there are slight differences between them. Michel Ponsich, the excavator, only mentioned inhumation burials for both cemeteries, but for the Djebila necropolis it is likely that cremation burials also existed, which were probably not recognised during his excavation. The burial customs are similar to those of the Iberian Peninsula and there appear to have been close links between the two regions. The main occupation period of both necropolises was very probably in the 6th century BCE. The finds show many foreign Mediterranean elements, although the question of whether objects were perhaps also made in the region north of the Atlas Mountains by specialized craftsmen cannot be answered at this stage. The processing and analysis of the finds has not yet been completed, so this should be regarded as a preliminary report. Pottery is present in only 30 % of the tombs at Aïn Dalia Kebira and Djebila. Of particular note is the presence of handmade vessels ›à chardon‹ from the end of the 8th and mainly the 7th century BCE, as well as two small Cruz del Negro type urns, one from each necropolis, and very few fragments of red-slipped Phoenician pottery, including the lower base of a  possible dipper jug, and part of the body and the start of the neck of a probable oinochoe with a trilobed rim. The project to re-examine the Phoenician-Punic cemeteries of Djebila and Aïn Dalia Kebira also involves the integration of scientific analyses and restoration works. By analysing some of the amber finds from the Djebila cemetery, Baltic amber from the Early Iron Age was identified for the first time in the area north of the Atlas Mountains. The restoration works revealed many decorations on objects, remains of textile fibre, and certain types of metalworking skills.